Benchmarking of RDBMS and NoSQL performance on unstructured data - Karimi, Mwai (2020)
New requirements are arising in the database field. Big data has been soaring. The amount of data is ever increasing and becoming more and more varied. Traditional relational database management systems have been a dominant force in the database field but due to the massive growth of unstructured and multiform data, firms are now turning to architectures that have scaleout capabilities using open source software, commodity servers, cloud computing and services like Database as a Service. Due to this, relational databases ought to adopt and meet these new data requirements with easier and faster data processing capabilities and also provide multiple analytical tools that have the possibility of displaying analytics instantly. This study aims to benchmark the performance of relational systems and NoSQL systems on unstructured data.